Perlindungan Transkrip Akademik Mahasiswa dengan Kombinasi Algoritma Rijndael dan SHA-3 - Amsal Hamonangan Butarbutar,; Ida Bagus Gede Dwidasmara, (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
This paper addresses the issue of securing academic transcripts for students by utilizing a combination of Rijndael encryption algorithm and Secure Hashing Algorithm-3 (SHA-3). The primary purpose is to enhance the protection and integrity of academic records against unauthorized access and tampering. SHA-3 is selected for its advanced cryptographic capabilities, surpassing its predecessors in security and efficiency. When combined with the Rijndael algorithm, which serves as the foundation for the Advanced Encryption Standard (AES), the system achieves robust encryption and data integrity verification. Through comprehensive design, implementation, and testing phases, the study demonstrates that the proposed method is effective in safeguarding academic transcripts. The results indicate that the system not only ensures data security but also operates efficiently. This research provides a valuable reference for further development and implementation of secure academic data management systems.
Keywords: Rijndael, SHA-3, Academic Transcript, Cryptography